Pengaruh Green Accounting Dan Carbon Emission Disclosure Terhadap Nilai Perusahaan Dengan Corporate Social Responsibility Sebagai Variabel Moderasi Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Fitri Rahmadani Nainggolan; Lusi Elviani Rangkuti; Mas’ut Mas’ut (Innovative: Journal Of Social Science Research, 2025)
This study seeks to assess the impact of green accounting and carbon emission disclosure on company value, as well as to evaluate whether corporate social responsibility moderates this influence within Food and Beverage Sub-Sector Manufacturing companies listed on the Indonesia Stock Exchange. This study's population comprised 36 Food and Beverage Sub-Sector Manufacturing firms registered on the Indonesia Stock Exchange. The sample was chosen using purposive selection, namely comprising 22 Food and Beverage Sub-Sector Manufacturing firms registered on the Indonesia Stock Exchange. This study employs multiple linear regression analysis utilizing SPSS 23 software. The study's findings demonstrate that green accounting exerts a negative and negligible impact on corporate value. The disclosure of carbon emissions exerts a negative and negligible impact on corporate value. The variables of green accounting and carbon emission disclosure concurrently exert a favorable and considerable influence on corporate value. The corporate social responsibility variable does not influence the relationship between green accounting and firm value. The corporate social responsibility variable does not influence the relationship between carbon emission disclosure and firm valuation. Corporate social responsibility variables do not concurrently impact the relationship between green accounting and carbon emission disclosure and firm value in Food and Beverage Sub-Sector Manufacturing Companies listed on the Indonesia Stock Exchange from 2019 to 2023.